341 Up-regulation of wound healing pathway may trigger adipogenic potentials of intramuscular progenitor cells in Wagyu as compared to Angus cattle. (5th December 2019) - Du, Min; Zhou, Xiang; Fu, Xing; Zhang, Yangzi; Zhang, Shuwen; Michal, Jennifer J; Wang, Hongyang; Jiang, Zhihua
Abstract: Marbling and muscle growth are significantly different between Angus and Wagyu cattle, but the underlying mechanisms remain unclear. The objective of the present study was to unravel genetic information flows specific to each phenotype. Biopsies of the Biceps femoris muscle were collected from three animals per breed. Intramuscular progenitor cells were isolated from the biopsies and alternative polyadenylation (APA) events were profiled using the WTTS-seq (whole transcriptome termini site sequencing) method. In adipogenic progenitor cells, 271 and 341 differentially expressed (DE) APA sites were identified as upregulated in Angus and Wagyu, respectively (adjusted P < 0.1). Pathway enrichment revealed that cellular wound healing events are unique to Wagyu. For these seven pairs of gene family members (in a broad sense), AKT1, CD47 and CD99, IGFBP3, KIF3A, RIOK1, RUNX1 and THBS1 were upregulated in Angus, while AKT3, CD59 and CD200, IGFBP2 and IGFBP4, KIF3B, RIOK3, RUNX2 and THBS2 were upregulated in Wagyu. There were 313 and 171 upregulated DE-APA sites in satellite cells derived from Angus and Wagyu, respectively (adjusted P < 0.1). Muscle system related pathways were enriched specifically for Angus. The CAPZA1, FAM227B, LDB2 and TTLL4 genes contained at least one DE-APA site that was specifically abundant in Angus or Wagyu. For these six gene family member pairs, ANKRD1, CD82, FBXO17, IGFBP2, PDLIM3 and THBS1 were abundantly expressed in Angus, but ANKRD28, CD9, CD14 and CD164, FBXO33, IGFBP5, PDLIM1 and THBS2 were upregulated in Wagyu. In brief, intramuscular progenitor cells and satellite cells may be characteristically different between Angus and Wagyu. Based on DE-APA events, the myogenesis pathways are enriched in cells from Angus, but the adipogenesis pathways are dominant in cells derived from Wagyu. This research was supported by the USDA-NIFA under Award Numbers 2016-67015-24470/2018-67051-27500 to ZJ and 2015-67015-23219/2016-68006-24634 to MD.